One‐Pot Cannizzaro Cascade Synthesis of ortho‐Fused Cycloocta‐2, 5‐dien‐1‐ones from 2‐Bromo(hetero)aryl Aldehydes. Issue 36 (29th July 2015) - Burroughs, Laurence; Eccleshare, Lee; Ritchie, John; Kulkarni, Omkar; Lygo, Barry; Woodward, Simon; Lewis, William
Abstract An intramolecular Cannizzaro‐type hydride transfer to an in situ prepared allene enables the synthesis of ortho‐fused 4‐substituted cycloocta‐2, 5‐dien‐1‐ones with unprecedented technical ease for an eight‐ring carboannulation. Various derivatives could be obtained from commercially available (hetero)aryl aldehydes, trimethylsilylacetylene, and simple propargyl chlorides in good yields.